แนวคิดทฤษฎีกิจกรรม : กรณีศึกษาแฟ้มสะสมผลงานอิเล็กทรอนิกส์แบบสะท้อนคิด - เวชโช สุธนิต; ณ สงขลา ใจทิพย์ (An Online Journal of Education, 2018)
In the current social transformations and endlessly multifaceted interaction activity is highly need a social psychology perspective as a framework to describe the phenomenal. The deep understanding of social structure that dialectically link the individual and community is the explicit pathway to clarify this issue. One of the theories that cover all dimensions is Activity Theory as a multidisciplinary framework that study the human activity both tools human and history together to identify the learning perspective of subject via individual and result in learning via community in the big picture. By using questions and test the ideas between each other in the activity system with the clear division of functions. This article reveals the application of activity theory in various ways and provides the explicit case study using reflective E-Portfolio to make the theory clearer.